ANALISIS KETELITIAN HASIL PEMERUMAN PERAIRAN DANGKAL MENGGUNAKAN MULTIBEAM ECHOSOUNDER - Angkoso Dewantoro; LM. Sabri; Bandi Sasmito (Departement Teknik Geodesi Universitas Diponegoro, 2012)
The activities of the underwater gas pipelaying takes bathymetry data as the imaging of seabed surface. Bathymetry data will be used at planning and implementing of the installation of gas pipeline owned by PT Nusantara Regas. In the implementation of data retrieval, PT Nusantara Regas choose PT Calmarine as the executor of the work. At the time of the surveying and reporting, PT Nusantara Regas have the right to check the accuracy of the Bathymetry’s results. IHO as international organizations in the hydrography sector has established procedures standardization for data collection and Bathymetry’s level order from the data which generated in those activities. Installation of equipment and calibration processes are also required to follow the procedures from the IHO and data retrieval software guide. In this research, the data was take using the Multibeam Echosounder (MBES) branded Elac Seabeam 1180, while the retrieval software and data processing using HYPACK software. All the surveying activities was held in Muara Karang and Bay Jakarta waters. Precision inspection process carried out by calculating the difference between the main lanes of Multibeam Echosounder (MBES) measuring data and Bathymatry cross line which measured using Singlebeam Echosounder (SBES). With the formula was performes the calculations on the data using a Multibeam Echosounder (MBES) and the Singlebeam Echosounder (SBES) cross line data which give the results that included to the order 1 of IHO accuration level. Keywords : Bathymetry, Multibeam Echosounder (MBES), IHO Standarts